THE USE OF INTERNET AMONG MALAYSIAN LIBRARIANS - Singh, Diljit (Malaysian Journal of Library and Information Science, 1998)
The Internet is fast becoming an important tool for librarians. The purpose of this study was to determine how librarians in Malaysia use the Internet for work-related purposes. A questionnaire was sent to 158 librarians, and 83 usable responses were received. The main findings indicated 90% of the respondents used the Internet for work-related purposes. The majority were recent users and had first learned to use it, from a friend or colleague, although they had also attended some formal training sessions. The users spent an average of 45.8 minutes per access, and averaged 6.97 hours per week on the net. All of them used the WWW, with the majority using it at least once a day, while 97.3% used the e-mail, 62.0% used Telnet, 31.5% used file transfers and 28.2% used newsgroups. A vast majority regarded the Internet as essential tool for librarians and felt that it had contributed to increased efficiency in their workplace. The main problem faced was the lack of time.